Advances in epidemiological status and pathogenesis of dental fluorosis - Zhang, Kaiqiang; Lu, Zhenfu; Guo, Xiaoying (Frontiers in Cell and Developmental Biology, 2023)
Fluoride is commonly consider as a “double-edged sword” because low consumption of fluoride can effectively prevent dental caries, but excessive consumption of fluoride can cause fluorosis. Dental fluorosis (DF) is a characteristic feature of fluorosis in the oral cavity that is manifested as tooth color changes and evident enamel defect. Presently, the pathogenesis of DF remains unclear. Herein, we have summarized the research progress in the pathogenesis and mechanism of DF in the past 5 years.